Enhancing production capacity with overall equipment effectiveness in manufacturing industry - Abdul Rasib, Amir Hamzah; Mohd Shablee, Fadhli Ariffin; Boejang, Hambali; Mohamad Rafaai, Z.F. (2024)
This study investigates the role of Overall Equipment Effectiveness (OEE) in enhancing the efficiency and reliability of manufacturing equipment. It aims to quantify equipment performance through availability, performance, and quality metrics to achieve world-class OEE rates. The research focuses on three objectives: identifying the six significant loss factors in manufacturing, applying OEE measures in production assembly, and proposing strategies to improve production capacity based on OEE findings. Utilizing data collection and analysis techniques such as Why-Why Analysis, Cause and Effect Diagrams, and Six Big Losses analysis, the study highlights the importance of OEE in optimizing the Automated Production Line (APL5) in the automotive industry. The findings suggest that implementing OEE can effectively address the six big losses, thereby enhancing production capacity and operational performance.